Behavior of high strength concrete – filled hybrid large – small rupture strains FRP tubes. (15th April 2020) - Nain, Monika; Abdulazeez, Mohanad M.; ElGawady, Mohamed A.
Highlights: High strength concrete filled FRP tubes under cyclic axial compression were investigated. The FRP were either small rupture strain (SRS), large rupture strain (LRS), or hybrid. The LRS-FRP were polyethylene naphthalate (PEN) and polyethylene terephthalate (PET). The results consist of ductility, ultimate strain, strength improvement, and energy dissipation. LRS-FRP improved the ductility, energy dissipation, and ultimate strength of the confined concrete. Abstract: This paper experimentally investigates the behavior of concrete filled fiber reinforced polymer (FRP) tubes (CFFTs) under cyclic axial compression. The FRP used in this study was either small rupture strain FRP (SRS-FRP), large rupture strain FRP (LRS-FRP), or hybrid LRS-FRP and SRS-FRP. LRS-FRPs are manufactured out of polyethylene naphthalate (PEN) and polyethylene terephthalate (PET). LRS-FRP has a high tensile rupture strain (usually greater than 5%) compared to 1–2% for SRS-FRP. The behavior of the investigated cylinders is presented in terms of ductility, ultimate strain, strength improvement, and energy dissipation. The results showed that using LRS-FRP significantly improved the ductility and ultimate strength of the confined concrete compared to SRS-FRP confined concrete. This study also carried out a comparison between the attained strengths, as well as the ultimate axial strain and the existing analytical models. A critical assessment of recent models has been made to suggest two models be implemented for predicting the ultimate stress–strain behavior of hybrid LRS-FRP.